IMPACT OF THE COVID-19 CORONAVIRUS PANDEMIC ON THE FINANCIAL STABILITY OF THE BANKING SECTOR IN KAZAKHSTAN - Kodasheva, G.S.; Azhmuxamedova, A.A.; Arynova, Z.A.; Shaikenova, N.Т.; Kabdullina, G.К.; Savanchiyeva, A.S.; Amerzhanova, D.A. (Scientific Journal of Pedagogy and Economics, 2020)
The coronavirus pandemic has led to the closure of the country's borders and social isolation of the population, which affected the decrease in loans allocated by banks to the population and business. Despite the increase in net profit by bankers, negative trends are being traced in this segment of the financial market under the influence of the coronavirus pandemic. The current crisis really has no analogues in world history, or we simply do not know about them (if, for example, the civilization that is now present on the planet Earth had predecessors). It is not like the previous ones by its very nature. Previous crises have always been based on a kind of long-term economic imbalance, but today (although with all the signs of the latter) we are faced with the coronavirus pandemic - an event whose scale and consequences turned out to be difficult to predict in principle. For this reason, no one really had the opportunity to prepare for what was happening. Temporary regulatory easing and a decrease in macroprudential markups will allow banks to gradually adapt to the situation and maintain financial stability. It is very important that banks and other financial institutions use indulgences to stabilize their financial position and lend to the economy, and not to pay dividends to owners and bonuses to management.